2018
DOI: 10.1155/2018/7803426
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Different Recording Lengths of Dynamic Cerebral Autoregulation: 5 versus 10 Minutes

Abstract: We compared the dynamic cerebral autoregulation (dCA) indices between 5- and 10-minute data lengths by analyzing 37 patients with ischemic stroke and 51 controls in this study. Correlation coefficient (Mx) and transfer function analysis were applied for dCA analysis. Mx and phase shift in all frequency bands were not significantly different between 5- and 10-minute recordings [mean difference: Mx = 0.02; phase shift of very low frequency (0.02–0.07 Hz) = 0.3°, low frequency (0.07–0.20 Hz) = 0.6°, and high freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 29 publications
(33 reference statements)
1
27
2
Order By: Relevance
“…The reliability of Mxa has previously been assessed in healthy volunteers in several studies, which have reported highly variable repeatability and reproducibility ranging from poor to excellent (Chi et al, 2018;Lee et al, 2020;Lorenz et al, 2007;Mahdi, Nikolic, Birch, Olufsen, et al, 2017), and from poor to good (Lorenz et al, 2008;Ortega-Gutierrez et al, 2014;Riberholt et al, 2021), respectively. As a potential explanation, these studies utilized short recordings, often shorter than 6 min, the minimum duration necessary for Mxa to stabilize according to one study .…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of Mxa has previously been assessed in healthy volunteers in several studies, which have reported highly variable repeatability and reproducibility ranging from poor to excellent (Chi et al, 2018;Lee et al, 2020;Lorenz et al, 2007;Mahdi, Nikolic, Birch, Olufsen, et al, 2017), and from poor to good (Lorenz et al, 2008;Ortega-Gutierrez et al, 2014;Riberholt et al, 2021), respectively. As a potential explanation, these studies utilized short recordings, often shorter than 6 min, the minimum duration necessary for Mxa to stabilize according to one study .…”
Section: Introductionmentioning
confidence: 99%
“…However, PRx, being a simple correlation coefficient, is noisy due to its indiscriminate nature and inherent, incoherent, physiological variability of ABP and ICP (Diedler et al 2011;Brady et al 2012). Transfer function analysis and other frequency methods have also been developed to assess CA (Tzeng et al 2012;Tzeng & Ainslie, 2014;Tian et al 2016;Labrecque et al 2017;Chi et al 2018;van der Scheer et al 2018). However, these methods are based on the assumptions of linearity and stationarity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Though the influence of recording duration on dCA estimates has been previously reported (Deegan et al, 2011;Mahdi et al, 2017;Chi et al, 2018), to our knowledge, this is the first study to show the effects of shortening recording duration on ARI estimates in both healthy controls and a disease population. Overall, our results show that the ARI did not change within each group when recording durations were gradually reduced from 5 to 1 min, and that the ICC remained high when taking into account other studies of the reproducibility of dCA metrics (Brodie et al, 2009;Sanders et al, 2018;Tzeng et al, 2012).…”
Section: Main Findingsmentioning
confidence: 67%
“…Mahdi et al (2017) shortened recordings from 16 min to 1 min, studying the stability of three parameters (ARI, Mx and TFA phase), and concluded that the minimum recording duration in healthy subjects should not be <3 min. Chi et al (2018) compared dCA indices (Mx and TFA) of AIS patients and controls between 5 and 10 minute signal lengths, but did not report any significant differences between dCA indices derived with these two different durations. In our study, we used the first 1, 2, 3, or 4 min of a good quality 5 min recording to simulate the effects of signal loss.…”
Section: Methodological Aspectsmentioning
confidence: 93%